2005
DOI: 10.1002/chin.200548017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in Chabazite Zeolite Frameworks.

Abstract: Sorption G 6000Hydrogen Storage in Chabazite Zeolite Frameworks. -As revealed by volumetric H2 uptake measurements and transmission IR experiments of H2 adsorption, proton exchanged chabazitic frameworks represent, among zeolites, the most efficient materials for hydrogen storage. Within the series of the considered materials, H-SSZ-13 exhibits the best behavior in terms of hydrogen uptake. A proper balance between available space (volume accessible to hydrogen), high contact surface, and specific interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…A general chemical formula of zeolites is represented as Recent studies have shown that zeolites can be potential materials for reversible hydrogen storage [6][7][8][9][10][11][12][13][14][15]. Du and Wu reported hydrogen adsorption capacity of 2.55 wt% for NaX at 77 K and 70 bar pressure [7].…”
Section: Introductionmentioning
confidence: 99%
“…A general chemical formula of zeolites is represented as Recent studies have shown that zeolites can be potential materials for reversible hydrogen storage [6][7][8][9][10][11][12][13][14][15]. Du and Wu reported hydrogen adsorption capacity of 2.55 wt% for NaX at 77 K and 70 bar pressure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also at cryogenic temperatures and 15 bar gravimetric storage capacities of 2.19 wt% was reported for Ca exchanged X zeolite [32]. However, hydrogen adsorption on zeolites at room temperature and 60 bar was reported less than 0.5 wt% [34,40].…”
Section: Zeolitesmentioning
confidence: 98%
“…However, hydrogen adsorption on zeolites at room temperature and 60 bar was reported less than 0.5 wt% [34,40]. It was shown that the amount of hydrogen adsorbed on zeolites depended on the framework structure, composition, and acid-base nature of the zeolites [32]. …”
Section: Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, zeolite is a promising adsorbentand has great potential for hydrogen storage, etc. [99,100]. Zeolite is recognized as an ideal membrane material for gas separation because some zeolites have the unique pore aperture sizes (0.3-1.3 nm) that are comparable to the scale of gas molecules [101,102].…”
Section: Zeolite Membranesmentioning
confidence: 99%